Max Weber’s Degree-Based Concept of the State and Its Impact on Political Sociology - Andreas Anter (Historicka Sociologie)
The modern state is a form of political rule that has emerged over the course of centuries. In the past and present, states are not static or uniform entities, but differ considerably in their stability, assertiveness and legitimacy. It was Max Weber who first formulated the insight that the existence of the state is always a matter of degree. With this approach, he breaks new ground in state theory and laid the foundations for the historical study of the emergence of the state as well as for the comparative analysis of its today’s threats. This goes particularly for the monopoly on violence, the central feature of the state. Weber developed his approach by strictly distancing it from the contemporary juridical theory of the state, which he accused of turning the state into a thing-like entity. The article shows that Weber is essential for the historical study of the emergence of the modern state as well as for the analysis of its current threats.